2012
DOI: 10.1007/s00441-011-1313-4
|View full text |Cite
|
Sign up to set email alerts
|

The laser lesion of the mouse visual cortex as a model to study neural extracellular matrix remodeling during degeneration, regeneration and plasticity of the CNS

Abstract: CNS lesions generally result in impaired function because regeneration of the adult CNS of mammals is poor. A variety of lesion models has been described that serve to further the understanding of the pathophysiology of the damaged tissue. A central cause of aborted regeneration is the glial scar that expresses a plethora of extracellular matrix molecules. Some of these are considered inhibitors of axon growth and regeneration. The laser lesion of the cortex offers the advantage that a circumscribed lesion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 152 publications
(152 reference statements)
0
21
0
Order By: Relevance
“…Here it was observed that the cells show a specific spatial distribution. For example, focal laser lesions in the adult mouse visual cortex (Roll et al, 2012) induce GFAP upregulation in a wide area, whereas the progenitor markers Vimentin and even more extremely Nestin are restricted to an area near the lesion core (Figure 1). Interestingly, astrocytes (type B cells) are the stem cells of the subventricular zone (SVZ) and are also positive for Nestin and Vimentin (Doetsch et al, 1997, 1999).…”
Section: Lesions Of the Central Nervous System Activate Endogenous Prmentioning
confidence: 99%
See 3 more Smart Citations
“…Here it was observed that the cells show a specific spatial distribution. For example, focal laser lesions in the adult mouse visual cortex (Roll et al, 2012) induce GFAP upregulation in a wide area, whereas the progenitor markers Vimentin and even more extremely Nestin are restricted to an area near the lesion core (Figure 1). Interestingly, astrocytes (type B cells) are the stem cells of the subventricular zone (SVZ) and are also positive for Nestin and Vimentin (Doetsch et al, 1997, 1999).…”
Section: Lesions Of the Central Nervous System Activate Endogenous Prmentioning
confidence: 99%
“…A similar finding of Nestin-expressing cells in a distinct pattern was made in the spinal cord after hemitransection and was also interpreted as local activation (Lang et al, 2004). Re-expression of the ECM molecule TN-C, which is expressed during development and later downregulated in the adult cortex, is also restricted to astrocytes located near the lesion (McKeon et al, 1991; Roll et al, 2012). It can be assumed that gradients of signaling molecules with high concentrations near the lesion and decreasing levels in the periphery influence the cell fate and result in the observed regional differences.…”
Section: Lesions Of the Central Nervous System Activate Endogenous Prmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first article of this section by Roll et al (2012), a new cortical laser lesion model to investigate remodelling of neural ECM during CNS degeneration, regeneration and plasticity is introduced. The particular advantage of this injury model is the non-invasive mode of cortical lesioning.…”
Section: Ecm In Axon Regeneration and Plasticitymentioning
confidence: 99%